Assessing the habitat and functional connectivity around fenced ecosanctuaries in New Zealand. (January 2021) - Burge, Olivia R.; Innes, John G.; Fitzgerald, Neil; Guo, Jing; Etherington, Thomas R.; Richardson, Sarah J.
Abstract: Fenced ecosanctuaries are a high-cost method of creating areas of pest predator-free habitat for species or populations for whom predation is a limiting factor. Past research has focused on 'inside the fence' habitat and bird populations, overlooking the potential for ecosanctuaries to augment bird populations 'outside the fence'. We assessed the amount of habitat around both fenced and unfenced ecosanctuaries in New Zealand, how connected the ecosanctuaries were to the wider landscape, and the overall landscape connectivity around ecosanctuaries, for six bird species at 18 sites (15 fenced; 3 unfenced), assuming a predator-free landscape. We found low levels of high-quality habitat around many fenced ecosanctuaries. There was no high-quality habitat at all around some ecosanctuaries for several bird species. Ecosanctuaries on peninsulas (with reduced fencing costs) tended to have a smaller proportion of the surrounding area in habitat and lower functional connectivity than unfenced ecosanctuaries and ring-fenced sites; meaning the reduced fencing costs at peninsular sites needs to be balanced against less habitat, on average, beyond the ecosanctuary. Managers deciding where to locate ecosanctuaries need to consider both the ecosystems within and those surrounding the site, and connectivity between the two. New Zealand is a world leader in fenced ecosanctuaries; lessons learned from this study in New Zealand are likely to apply elsewhere, where the use of fenced ecosanctuaries for predation sensitive species is incipient.